A case report of Takayasu’s arteritis with stroke as initial presentation - Islam, Mohammad Sirajul; Hossain, Ahmed; Islam, Md Daharul; Bala, Chandra Shekhar; Rahman, Aminur; Abira, Mahmuda; Islam, Md Ranaul; Mahmud, Khaled; Sarker, Partha Sarothi (Bangladesh Journal of Medicine, 2023)
Takayasu’s arteritis a rare, idiopathic, chronic granulomatous vasculitis that affects aorta and its major branches. Stroke is a common complication; however, this is hardly the initial presentation.Here we reported one such case of a 39-year-old man presented with sudden onset right sided hemiparesis, facial deviation towards the left and motor aphasia for last 21 days. He was diagnosed as ischemic stroke with right sided hemiparesis with motor aphasia due to Takayasu’s arteritis. Bangladesh J Medicine 2023; 34(2): 143-146